A case study of 38 micro‐organic pollutants contamination in Kirmir Stream, Turkey. Issue 4 (11th October 2021) - Arslan, Pınar; Ozeren, Saniye Cevher
Abstract: Environmental micro‐organic pollutants accumulate in abiotic parts of the aquatic ecosystems. This study was aimed to make residue, source, and composition profiles of some micro‐organic pollutants, consisting 16 polycyclic aromatic hydrocarbons (PAHs), seven polychlorinated biphenyls (PCBs), nine organochlorine pesticides (OCPs), and six polybrominated diphenyl ethers (PBDEs) in water and sediment from Kirmir Stream (Ankara, Turkey) between 2017 and 2018 as seasonal based. In water and sediment samples, total PAHs were determined to be 15.68 and 1216.19 μg/kg, respectively. Among the OCPs, only DDE was detected in sediment samples and its total concentration was 1768.92 μg/kg. Other OCPs, PCBs, and PBDEs were below the limit of quantification. Having molecular structure, found PAHs in water and sediments were originated from pyrolytic and petrogenic. Thus, this study will be very useful to provide background information for further studies on the contamination with environmental micro‐organic pollutants in the region.